2010
DOI: 10.1007/s11426-010-4039-3
|View full text |Cite
|
Sign up to set email alerts
|

Levels, trends and risk assessment of arsenic pollution in Yangzonghai Lake, Yunnan Province, China

Abstract: The arsenic contamination accident in Yangzonghai Lake, Yunnan has been of wide concern. In order to investigate the arsenic distribution and concentration trends after the accident, samples including lake water, sediments, soil, aquatic organisms and crops were collected in November 2008, as well as in February, May and September 2009. The average arsenic concentrations (arithmetic average) in lake water in the four sampling events were 176.9, 147.3, 159.3, and 161.1 g/L, while those in the sediments were 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…Therefore, N. marina is functioning as a hyperaccumulator in As polluted aquatic ecosystems, such as Yangzonghai Lake in Yunnan Province. 27 According to Reeves and Baker, 28 Cd concentration in hyperaccumulator is greater than 100 mg kg −1 (0.01%). Concentrations of heavy metals in submerged macrophytes at site-species scale.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Therefore, N. marina is functioning as a hyperaccumulator in As polluted aquatic ecosystems, such as Yangzonghai Lake in Yunnan Province. 27 According to Reeves and Baker, 28 Cd concentration in hyperaccumulator is greater than 100 mg kg −1 (0.01%). Concentrations of heavy metals in submerged macrophytes at site-species scale.…”
Section: ■ Discussionmentioning
confidence: 99%
“…As now well known, water temperature stratification of lakes generally forms in summer and disappear in winter. The commentators try to deny the fact that total arsenic concentration changed with depth in their commentary by quoting the investigation results of Wang et al (2010). Unfortunately, none of the four investigations made by Wang et al were in the same month as we did.…”
Section: About the Concentration Distribution Of As In The Lakementioning
confidence: 72%
“…Besides microorganism's function, whether competitive anions also promoted desorption of As on iron(oxy)(hydr)oxides in the sediment of the lake needs further verification. (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, As contamination in aquatic environment is becoming a critical issue in several regions around the globe. For example, C aceres et al (1992) reported high As concentrations up to 21 mg L À1 in Lao River, Chile, Culioli et al (2009) found As concentrations of 18e2330 mg L À1 in Presa River, France, and Wang et al (2010) showed As levels of 147e177 mg L À1 in Yangzonghai Lake, China. The elevated As concentrations in aquatic environment are far above the USEPA provisional guideline value of 150 mg L À1 , potentially adversely impact aquatic environment (USEPA, 1999).…”
Section: Introductionmentioning
confidence: 99%